Anti-Spike SARS-CoV-2 IgG Assessment with a Commercial Assay during a 4-Month Course after COVID-19 Vaccination - Jakub Swadźba (MDPI AG, 2021)
We intended to assess the humoral response induced by the Pfizer/BioNTech Comirnaty COVID-19 vaccine with commercially available immunoassays: anti-spike (S) IgG and IgM, and anti-nucleocapsid (N) IgG antibodies, over a 4-month course. One hundred subjects, including 15 COVID-19 convalescents, comprised the study cohort. The SARS-CoV-2 antibodies concentrations were measured on day 0′ and 10′, 20′, 30′, 60′, 90′, and 120′ after the first dose administration. Over the course of the study, 100% of the participants developed and sustained anti-SARS-CoV-2 S IgG antibodies. The highest concentration, exceeding the quantification range of the test (2080 BAU/mL), was reached by 67% of the subjects on day 30′. The concentration of the antibodies remained stable between days 30′ and 90′ but was followed by a significant decrease between days 90′ and 120′. The stronger and more persistent humoral response was noted for women. The COVID-19 convalescents developed higher antibody levels, particularly 10 days after the first Comirnaty dose. Twenty-three out of the eighty-five naïve vaccinees failed to develop a detectable IgM response. LIAISON® SARS-CoV-2 TrimericS IgG (DiaSorin S.p.A, Saluggia, Italy) may be useful in the assessment of the humoral response to the Comirnaty vaccine. In contrast, Abbott’s anti-S SARS-CoV-2 IgM has a limited utility in this context.